Performance optimization and defect studies of Pb-free CsSnBr3-based perovskite solar cells - Nasrin T.; Mottakin M.; Selvanathan V.; Hossain M.I.; Shahiduzzaman M.; Islam M.A.; Ahamed M.S.; Alharbi H.F.; Akhtaruzzaman M. (Elsevier Ltd, 2024)
Perovskite solar cells (PSCs) have become increasingly popular in the photovoltaic industry due to their high power conversion efficiency (PCE) and potential for low-cost manufacturing. However, despite the significant promise of lead-based PSCs, several challenges must be addressed before commercialization can occur. These challenges include toxicity and defects. As such, this study focuses on optimizing an environmentally friendly (non-toxic) PSC based on CsSnBr3 perovskite material. To achieve this objective, we examined various factors that influence the performance of the PSC, such as material bandgap, transport materials, individual layer thickness, and defect density associated with temperature effects. We also conducted a thorough analysis of the photovoltaic performance of the device. Our findings reveal that bulk and interface defects significantly impact the device's performance. Through our investigation and analysis, we were able to design an optimized device that exhibits a PCE of 17.94 %. This impressive performance was accompanied by a short-circuit current density (JSC) of 18 mA/cm2, an open-circuit voltage (VOC) of 1.3 V, and a fill factor (FF) of 74.5 %. Throughout the study, we utilized SCAPS-1D simulations to conduct a detailed optoelectronic study and analyze the device's performance. Furthermore, we employed 3D finite-difference time-domain (FDTD) optical simulations to validate the optical performance of the optimized device. Our study demonstrates that lead-free PSCs have significant potential in photovoltaics. By optimizing the manufacturing process and addressing the challenges associated with these materials, we can unlock even more tremendous potential for this technology. Overall, our numerical study can be a valuable resource for researchers and industry professionals in this field. 2023 Elsevier Ltd